2011
DOI: 10.4315/0362-028x.jfp-10-545
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Listeria monocytogenes Isolated in Chicken Slaughterhouses in Northern Greece

Abstract: This study was conducted to determine the prevalence and antimicrobial resistance of Listeria monocytogenes recovered from chicken carcasses in slaughterhouses in Northern Greece. A total of 100 poultry samples (300 carcasses) were examined for Listeria spp. The samples were neck skin taken from four different slaughterhouses in Northern Greece. Forty samples were also taken from the environment of the slaughterhouses. Identification of L. monocytogenes was carried out by PCR and fingerprinting of the isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 30 publications
2
35
3
5
Order By: Relevance
“…The high incidence of L. monocytogenes in chicken liver is due to the fact that the product is supplied unpackaged; and could be contaminated during evisceration, transportation and marketing. In previous studies, the rate of contamination with L. monocytogenes in raw poultry products was found to be 22% in the Nordic countries (Gudbjörnsdóttir et al, 2004), 34% in Sri Lanka (Ganasena, Kodikara, Ganepola, & Widanapathirana, 1995), and 38% in northern Greece (Sakaridis et al, 2011); which are higher than the results of this study. However, the reported rate of L. monocytogenes contamination in Italy (Pesavento et al, 2010), Turkey (Yücel et al, 2005) and Jordan (Osaili et al, 2011) are consistent with our results.…”
Section: Prevalence Of Listeria Spp In Poultry Productscontrasting
confidence: 77%
See 2 more Smart Citations
“…The high incidence of L. monocytogenes in chicken liver is due to the fact that the product is supplied unpackaged; and could be contaminated during evisceration, transportation and marketing. In previous studies, the rate of contamination with L. monocytogenes in raw poultry products was found to be 22% in the Nordic countries (Gudbjörnsdóttir et al, 2004), 34% in Sri Lanka (Ganasena, Kodikara, Ganepola, & Widanapathirana, 1995), and 38% in northern Greece (Sakaridis et al, 2011); which are higher than the results of this study. However, the reported rate of L. monocytogenes contamination in Italy (Pesavento et al, 2010), Turkey (Yücel et al, 2005) and Jordan (Osaili et al, 2011) are consistent with our results.…”
Section: Prevalence Of Listeria Spp In Poultry Productscontrasting
confidence: 77%
“…particularly L. monocytogenes to ampicillin and penicillin (Table 2), the drugs of choice for treatment of listeriosis. Ayaz and Erol (2010) found that most of the L. monocytogenes strains isolated from ground turkey were resistant to ampicillin and penicillin, whereas the other researchers (Alonso-Hernando, Prieto, García-Fernández, Alonso-Calleja, & Capita, 2012;Davis & Jackson, 2009;Sakaridis et al, 2011) reported a high susceptibility of L. monocytogenes to these antimicrobials. The results of high antimicrobial resistance rate to fluoroquinolones (ciprofloxacin and enrofloxacin) and tetracycline in this study could be explained by the frequent use of these antimicrobials to treat infection in Iranian poultry farms.…”
Section: Antimicrobial Resistance Of Listeria Spp Isolatesmentioning
confidence: 94%
See 1 more Smart Citation
“…L. monocytogenes was found only in carcass swabs (CS, 26%) and samples obtained by the skin excision method (EX, 4%) almost all in Sa . The recovery of L. monocytogenes from fresh poultry is not surprising: in previous studies, the prevalence of L. monocytogenes in poultry ranged from 12 to 38% (Ganasena, Kodikara, Ganepola, and Widanapathirana, ; Gudbjörnsdóttir et al, ; Osaili et al, ; Pesavento, Ducci, Nieri, Comodo, and Lo Nostro, ; Sakaridis et al, ; Yücel, Çitak, and Önder, ). Although the post‐cooking contamination of RTE poultry products is prevalent and in general not poultry‐source derived (Osaili et al, ) raw poultry was confirmed as a potential source of L. monocytogenes contamination of RTE products after cooking (Bailey et al, ; Jamali et al, ; Uyttendale et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…Only one L. monocytogenes isolate originating from a boot sock sample was resistant to ciprofloxacin, but all isolates showed resistance to oxacillin and clindamycin. Resistance to oxacillin and clindamycin is common and reduced susceptibility to ciprofloxacin has also been reported (Pesavento et al., ; Sakaridis et al., ; Shen et al., ). However, tetracycline resistance, which has frequently been detected in L. monocytogenes isolated from poultry and poultry products, was not found in our study (Sakaridis et al., ; Shen et al., ).…”
Section: Discussionmentioning
confidence: 99%